Sarcopenia Associated with Cognitive Frailty in Adults Diagnosed with Diabetes: Evidence from Primary Healthcare Centers - Laurentius Johan Ardian; Fitria Kusuma Wardhani; Bisarda Kanira; Aura Cinta Jihada; Tia Maya Affrita (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Recent clinical investigations have drawn attention to cognitive frailty as a composite syndrome that occurs with increasing frequency in populations affected by chronic metabolic disorders, most notably type 2 diabetes mellitus. Despite this recognition, empirical data characterizing its prevalence and predisposing determinants among younger, community-dwelling adults with diabetes remain insufficient. Objective: The aim of this investigation was to determine whether sarcopenia independently contributes to the occurrence of cognitive frailty in adults with diabetes managed within the primary care system. Methods: Adopting a cross-sectional design, the study recruited 281 adults living with diabetes from two community-based health facilities. The Mini-Mental State Examination (MMSE) served as the primary cognitive assessment tool, and the SARC-F questionnaire—a validated self-report screening instrument rather than a direct physiological measure of muscle mass or handgrip strength—was used to assess sarcopenia risk. Chi-square analysis tested bivariate associations, and adjusted prevalence ratios (PRs) were computed using modified Poisson regression with robust variance, an approach suited for cross-sectional data in which outcomes are not rare. Results: The overall prevalence of cognitive frailty in the study cohort was 3.2%. In multivariate models, sarcopenia was associated with a significantly higher likelihood of cognitive frailty (adjusted PR = 6.84; 95% CI: 1.55–30.19). Conclusion: Sarcopenia is a clinically meaningful, independent risk factor for cognitive frailty in community-dwelling adults with diabetes. Integrating parallel assessments of sarcopenia and cognitive function into routine primary care diabetes management may improve early detection and help reduce downstream adverse health outcomes.